Examen especial a la gestión administrativa de la unión provincial de cooperativa de transporte de pasajeros Los Ríos y su incidencia en los resultados del año 2012 - Luna Vélez, Dolores Elizabeth (2013)
Land transport in the Ecuador is considered to be a strategic sector for the national Government, this is that thousands of people every day have to make use of this means of transport to be able to move from one place to another. The Provincial transport cooperative Union of passenger Los Rios provides the service of transporting citizens of good faith, Quevedo and Mocache cantons daily to their places of work and studies. Under this context proposes the need to analyse it management administrative of the Union Provincial cooperative of transportation of passengers rivers; allow collect relevant information to detect existing control problems and propose the changes necessary to compete in a sustainable way in the long term in the local transportation market, which will enable its partners have higher income and welfare for theirs. This study raises a research identifying the demands and growing needs of citizens who use public transport as a means of mobilization, to be implemented in administrative management and control of the Union, Provincial cooperative transportation of passengers Los Rios. To be noted, that most important of this project is to analyze the administrative management and to draw conclusions that allow the directors of the cooperative have a functional administrative structureto develop the activities planned with the optimum use of resources, especially human resources, because it is they who are daily dealing with citizens that are uploaded to transport units.This control to the fulfilment of the objectives and plans set out by the members of the cooperative; defining and establishing standards that can measure the performance and, if there are deviations, determine the causes of the same and take the necessary corrective measures for the normal development of the institution.